2022
DOI: 10.1101/2022.03.16.22272511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monoclonal antibody and antiviral therapy for treatment of mild-to-moderate COVID-19 in pediatric patients

Abstract: The recent surge of SARS-CoV-2 Omicron variant (B.1.1.529) coincided with new treatment options for mild-to-moderate Covid-19 in high-risk adolescents and adults. In this report we describe patient characteristics, treatment-related process measures and outcomes associated with early Covid-19 therapy in high-risk pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Finally, 37 studies were eligible for review by full text. Twenty-three studies [6][7][8][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] involving 314 353 patients were included in the meta-analysis. All included studies except one 7 were retrospective.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 37 studies were eligible for review by full text. Twenty-three studies [6][7][8][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] involving 314 353 patients were included in the meta-analysis. All included studies except one 7 were retrospective.…”
Section: Search Resultsmentioning
confidence: 99%
“…Five studies 7,19,28,31,33 involving 2143 patients reported the incidence of adverse events in patients. The pooled analysis showed no significant difference between the two treatment groups in terms of F I G U R E 1 Preferred Reporting Items for Systematic reviews and Meta-Analysis flow diagram of the included studies in the meta-analysis the incidence of any adverse events in patients (OR = 2.20; 95% CI: 0.42-11.47; p = 0.34) (Figure 4).…”
Section: Safety Outcomesmentioning
confidence: 99%
“…Figure 1 shows the flow diagram of study selection according to its title, abstract, and full text. After removing duplicated records, seventeen studies, 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 (two RCTs and fifteen observational studies) with 27,429 patients were included in the meta‐analysis. The main characteristics of included studies are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Data are available online for the included studies. 19,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation